Rearrange the slope formula y = mx + b for the quantity of interest m. Make sure to show each step, but make them simple.

1 answer

To rearrange the slope formula \( y = mx + b \) to solve for \( m \), follow these steps:

  1. Start with the original equation:
    \[ y = mx + b \]

  2. Subtract \( b \) from both sides:
    \[ y - b = mx \]

  3. Now, to isolate \( m \), divide both sides by \( x \) (assuming \( x \neq 0 \)):
    \[ \frac{y - b}{x} = m \]

  4. Final result:
    \[ m = \frac{y - b}{x} \]

And that is how you rearrange the slope formula to solve for \( m \).